PARIWISATA; ANTARA TUNTUTAN INDUSTRI DAN KEARIFAN LOKAL - Karim, Abuya Busro (STAIN PAMEKASAN, 2012)
Abuya Busro Karim (Penulis, Bupati Sumenep periode 2010-2015. e-mail: busyrokarim@yahoo.com) Abstract This simple article reflects the condition of tourism in Madura, particularly in Sumenep region. The fact describes that it has not been easy to develop tourism place as it demonstratess in Bali. Toursim development must be natural (sunnatullah), however it finds any handicaps that needs wise response. Madurese tourism development must consider the following: Islam as the major religion of Madurese and the human resource. Hence, tourism must protect the local people become the victim of tourism industry. A good tourism industry is not only economic oriented but also it must gives substantial challenge to Islamic and Madures culture to take role in tourism industry. Kata-kata kunci pariwisata, budaya, Madura, Sumenep